(untitled) (Jurnal Geomine, 2021)
One of the factors that influence coal quality is the presence of clay bands in the coal sediment layer. The purpose of this study was to determine the depth and thickness of the clay bands in the coal seam according to the vertical log data. The research method used is an inductive method that uses a combination approach between qualitative and quantitative research, by combining the results of literature studies, field data which are all studied, analyzed, and synthesized comprehensively to conclude the series of studies that have been carried out. Based on the results of the research conducted, it was found that the depth (position) of the clay bands in the PDH41 seam 1 logging well was found at a depth of 30.40 - 31.40 meters with a thickness of 1 meter, clay bands at seam 2 were found at a depth of 34.80 - 35.80 meters with a thickness of 1 meter, PDH34 logging wells found clay bands at a depth of 71.20 - 71.80 meters with a thickness of 0.60 meters, PDH37 logging wells were covered with clay bands at a depth of 12.20 - 13.50 meters with a thickness of 1.3 meter. Of the 9 logging wells, 3 of them were detected with clay bands while 6 logging wells were not detected by clay bands.